2022
DOI: 10.1037/fam0000928
|View full text |Cite
|
Sign up to set email alerts
|

Strengths of the heart: Stressors, gratitude, and mental health in single mothers during the COVID-19 pandemic.

Abstract: The Coronavirus disease (COVID-19) pandemic has created significant economic, social, and mental health challenges for many parents. However, single mothers (who are typically both primary caregivers and wage earners for their families) may be especially vulnerable to stress and mental health problems during this crisis. Gratitude is strongly linked to positive emotions as well as mental health and has been shown to be amendable in interventions but has rarely been assessed in regard to parent well-being. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Other frequently reported effects on families were that parents felt constrained to allow excessive media use in the absence of other leisure activities, multiple burdens imposed by pandemic restrictions especially on mothers, and parents feeling overwhelmed by the supervision of homeschooling tasks. The burden experienced by mothers under COVID-19 has been reported in the literature (Calvano et al 2021 ; McLaren et al 2020 ; Taylor et al 2021 ), and mothers of children with depression or developmental disorders are known to be under extra strain (Babore et al 2021 ; Burnett et al 2021 ; Chafouleas and Iovino 2021 ; Wang et al 2021 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other frequently reported effects on families were that parents felt constrained to allow excessive media use in the absence of other leisure activities, multiple burdens imposed by pandemic restrictions especially on mothers, and parents feeling overwhelmed by the supervision of homeschooling tasks. The burden experienced by mothers under COVID-19 has been reported in the literature (Calvano et al 2021 ; McLaren et al 2020 ; Taylor et al 2021 ), and mothers of children with depression or developmental disorders are known to be under extra strain (Babore et al 2021 ; Burnett et al 2021 ; Chafouleas and Iovino 2021 ; Wang et al 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…Mothers, and single mothers in particular, were confronted with new challenges, and had to manage work at home, supervision of homeschooling as well as household chores. They were thus at risk for overload, exhaustion and depression (Calvano et al 2021 ; McLaren et al 2020 ; Taylor et al 2021 ). Spending more time in confined spaces also resulted in more frequent family conflicts and sometimes led to physical and sexual abuse or maltreatment (Rodriguez et al 2021 ; Sinko et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kehidupan keluarga dengan status single mother sangat berbeda dengan keluarga utuh. Oleh karena permasalahan tersebut maka akan berpengaruh terhadap pertumbuhan dan perkembangan anak (Kim & Brody, 2005;Taylor et al, 2021). Secara umum, single mother dapat diartikan orang tua tunggal yang mengasuh dan membesarkan anak mereka sendiri tanpa bantuan pasangan mereka, baik itu pihak suami maupun pihak isteri.…”
Section: Pendahuluanunclassified
“…As a result, income and employment hit worse for most women, who are more likely to be single parents than men. With that, they are likely to experience hardships and parenting problems due to these different stressors [5][6][7] Waldfogel et al [8] cited in the study of Taylor Z. E., [7]. Thus, this pandemic's economic, health, and socioeconomic situations have accelerated these circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…However, the uniqueness of this study is, that it does not focus on the mental health-related problems that most studies focus instead our study emphasizes on the economic trials faced by single parents during the pandemic in the city of Tacloban which is experiencing unemployment and having financial hardships as stated above while other studies have shown that most of the single parent's during the pandemic experiences having a mental health-related problem that sometimes affects their childcare, the effect caused by the COVID-19 pandemic had an overall impact on families' function, welfare, and the mental health problem, including depression and high levels of anxiety Almeida et al, 2020 [16]. The everyday family function and the groups that support them resulted in a significant shift in parents' anxiety and concern [17,18] cited in the study of Taylor et al [7].…”
Section: Introductionmentioning
confidence: 99%